Pengaruh ITO terhadap NPM pada Perusahaan Makanan dan Minuman di BEI (2013-2018) - Nurul Indah Fauziah; Dimas Sumitra Danisworo; Banter Laksana (Indonesian Journal of Economics and Management, 2021)
This research was conducted to test the level of influence of inventory turnover against Net Profit Margin in the companies of food and beverage listed on the IDX period 2013-2018. The objects used in this study are the financial statements of food and beverage companies listed on the IDX period 2013-2018. The population in this study amounted to 26 food and beverage companies and 5 samples were taken using purposive sampling techniques. The type of data used in this study is secondary data obtained from the company's official website. The independent variables used in this study are inventory turnover, whereas for the dependent variables used in this research is the NPM. The data analysis techniques used in this study are descriptive statistics analysis, simple linear regression analysis, and hypothesis testing using the help of SPSS software. The results showed significant supply turnover against NPM with an influence rate of 70,5%.